Optimizing public space design through odd-even policy: Reducing traffic congestion and pollution in DKI Jakarta - Azni, Isnatami Nurul; Prihantoro, Whidas; Saputra, Yana Anjana (Journal of Placemaking and Streetscape Design, 2024)
Background: The Provincial Government of DKI Jakarta issued Governor Regulation No. 155 of 2018 and its amendments regarding Traffic Restrictions with the Odd-Even System. This regulation aims to reduce congestion levels on 16 main roads. By decreasing congestion, the expected outcome is a reduction in air pollution levels in DKI Jakarta. However, there is concern that the implementation of Governor Regulation No. 155 of 2018 might lead to an increase in conventional car purchases, as affluent individuals may buy two cars with odd and even license plates. This choice is driven by the continued use of fossil fuel-based energy. This study aims to evaluate the effectiveness of Governor Regulation No. 155 of 2018 in reducing traffic congestion and air pollution in DKI Jakarta. Additionally, the study seeks to understand the relationship between the implementation of the odd-even traffic restriction system and electric vehicle sales. Methods: The research was conducted by analyzing secondary data obtained from government agencies and other institutions. Furthermore, a questionnaire survey was administered to individuals active on the 16 main roads where the odd-even policy is enforced. The study also analyzed the purchase levels of electric cars, which is one method for Jakarta residents to avoid fines on odd-even roads. Result: Based on the research findings, Governor Regulation No. 155 of 2018 and its amendments have not yet effectively reduced traffic congestion and air pollution in DKI Jakarta. Conclusion: The increase in electric car purchases potentially introduces new issues, such as the unsustainable management of nickel mines required for electric vehicle battery production. Therefore, other sustainable strategies are needed to address traffic congestion and air pollution. Novelty/Originality of the study: This study shows that Governor Regulation No. 155 of 2018 has yet to reduce congestion and air pollution in DKI Jakarta effectively. In addition, the increase in the purchase of electric cars as a solution to avoid fines has raised new problems related to the environmental impact of electric vehicle battery production.